HOW TO SOLVE THE PROBLEM OF FINDING THE GREATEST COMMON DIVISOR - ANTOS, Karel (Trends in education, 2015)
This article discusses the possibilities and ways of exploring mathematical problems. It shows that the research approach in the field of mathematical research is a method by which a teacher can not only teach, but which enables pupils and students to learn, make experiments and find different solutions of different mathematical problems. The creative element is shown here on the problems of finding the greatest common divisor of natural numbers.
Keywords: divisibility; integers; experimenting; proving; greatest common divisor.